Comparison of Trust Assessment Scales Based on Item Response Theory - Dai, Buyun; Zhang, Wenqing; Wang, Yang; Jian, Xiaozhu (Frontiers in Psychology, 2020)
Three widely used interpersonal trust measurement scales (ITS, RPHNS, CTS) have seldom been applied in non-Western contexts. Different social environments may lead to variation in the level or structure of trust. Therefore, it is necessary to compare the applicability of these scales to different levels of trust-related traits in Eastern cultures so that researchers can choose appropriate scales for relevant studies. This study conducted a comparative analysis of the ITS, RPHNS, and CTS. A sample of 725 Chinese college students was analyzed. Total score correlations and latent factor correlations estimated by confirmatory factor analysis for a first-order three-factor model were assessed, and then the quality of the item parameters, test reliability and standard errors, and test information were assessed. The results are as follows: (1) the three scales assess almost the same psychological traits; (2) the original structure of only the RPHNS is verified; (3) some items on the ITS do not work well, while the RPHNS and the CTS have higher overall test reliability; and (4) the average item information provided by the CTS is the highest across all trait levels. In most cases, the RPHNS is the best choice in the Chinese cultural context.